The dangers of Online Sports Betting - Pansanato, Matheus Bortolotto (2024)
Gambling addiction is already widely known as a mental health problem. Currently, online betting is gaining more fans due to its ease of access and the desire for financial profit. The integration of online betting with sports has increased the participation of Brazilians in online gambling and, consequently, the associated problems. For a few years now, several discussions about the regulation of online sports betting have been taking place in the country, and in May 2024 Brazil regularized gambling with the approval of PL 2.234/22, reversing a historic national ban. Due to football's strong cultural appeal, many betting sites have taken advantage of the lack of official regulation to attract a growing number of users. It is crucial to promote awareness of the risks and potential for addiction associated with online sports betting practices.